2016
DOI: 10.1097/pas.0000000000000597
|View full text |Cite
|
Sign up to set email alerts
|

High Expression of Intestinal Homing Receptor CD103 in Adult T-Cell Leukemia/Lymphoma, Similar to 2 Other CD8+ T-Cell Lymphomas

Abstract: We investigated the expression of the αEβ7 integrin (CD103)-intestinal homing receptor of T-intraepithelial lymphocytes (IELs) in 130 cases of adult T-cell leukemia/lymphoma (ATLL). We detected CD103 lymphoma cells in 55% (31/56) of mainly gastrointestinal (GI)-involved ATLL cases. Among them, lymphoma cells of 18 cases located in other involved organs had similar CD103 expression patterns. Histologically, we found (a) increased reactive IELs in non-neoplastic mucosal layers in 28% (5/18) of surgical and mucos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 31 publications
(30 reference statements)
1
13
0
Order By: Relevance
“…In 1/10 of healthy individuals, a distinct population of TCRγδ-expressing lymphocytes has been recognized[ 39 , 66 , 67 ]. It is indeed an integrin of the β7 family, precisely CD103, which is responsible for the adhesion of the T lymphocytes to epithelial cells[ 68 - 70 ]. If frozen tissue is available, immunohistochemical typing for TCRγδ of T lymphocytes can be performed.…”
Section: Iel-immunophenotypementioning
confidence: 99%
“…In 1/10 of healthy individuals, a distinct population of TCRγδ-expressing lymphocytes has been recognized[ 39 , 66 , 67 ]. It is indeed an integrin of the β7 family, precisely CD103, which is responsible for the adhesion of the T lymphocytes to epithelial cells[ 68 - 70 ]. If frozen tissue is available, immunohistochemical typing for TCRγδ of T lymphocytes can be performed.…”
Section: Iel-immunophenotypementioning
confidence: 99%
“…Neoplastic T/NK cells exhibiting CD103 were observed most frequently in gastrointestinal T cell lymphomas, especially in enteropathy‐associated T cell lymphoma (EATL) and MEITL, and were also found in a subset of cases of adult T cell leukaemia/lymphoma (ATLL) and epidermotrophic CD8 + mycosis fungoides (MF) . Ishibashi et al . reported one of the 10 intestinal EBV + TNKL cases (10%) to be positive for CD103, the positive ratio of which was concordant with that (10%) in our series.…”
Section: Discussionmentioning
confidence: 78%
“…CD103 is a marker for homing receptors of intra‐epithelial and lamina propria lymphocytes . Neoplastic T/NK cells exhibiting CD103 were observed most frequently in gastrointestinal T cell lymphomas, especially in enteropathy‐associated T cell lymphoma (EATL) and MEITL, and were also found in a subset of cases of adult T cell leukaemia/lymphoma (ATLL) and epidermotrophic CD8 + mycosis fungoides (MF) . Ishibashi et al .…”
Section: Discussionmentioning
confidence: 99%
“…Small intestinal MEITL mostly showed intramucosal spreading of lymphoma cells with neoplastic CD103 + and CD8 + T-IELs [9]. It was reported that lymphoma cells in 21 of 31MEITL (68%) as well as 31 of 56 GI ATLL patients (55%) showed expression of CD103 homing receptor of T-IELs, and ATLL had similar histopathological characteristics to MEITL with respect to increased atypical and reactive T-IELs [18]. The endoscopic ndings of MEITL have been reported as edematous mucosa with mosaic and diffuse mucosal thickening patterns, and shallow ulceration, as well as ulcerative type tumors in the small intestine [21].…”
Section: Discussionmentioning
confidence: 89%
“…Histologic examination was performed in biopsy specimens of the GI tract from all 27 TNKCL patients and in colorectal surgical specimens from seven. In addition to the cytohistological characteristics of tumors, two additional histologic ndings were examined due to similar features between MEITL and ATLL [18]. Medium-sized and large atypical lymphocytes with irregular nuclei in ltrating the epithelium were de ned as atypical intraepithelial lymphocytes (IELs).…”
Section: Histology and Immunohistochemistrymentioning
confidence: 99%